Pathomorphological Changes in the Liver of Goats Affected by Escherichia coli Infection - Saini, Priya; Meena, Sarjna; Saini, Priyanka; Saini, Pawan (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was aimed to document the gross and microscopic findings in the livers of goats from Jaipur region. A total of 712 liver samples were collected from organized slaughter houses and various meat outlets in Jaipur. Among these, 253 samples of liver exhibiting suspected abnormalities were selected for analysis. These samples were subjected to microbiological examination using MacConkey agar and eosin methylene blue agar, along with detailed histopathological evaluation. Esherichia coli infections were observed in 15 out of 253 samples accounting for an incidence rate of 5.93% E. coli infection in necropsied goat livers.